Analisis Dampak Fluktuasi Harga Kakao terhadap Tingkat Kesejahteraan Rumah Tangga Petani di Desa Kaleok Kecamatan Binuang Kabupaten Polewali Mandar - Ferdiansyah Himawan; Jusra Jusra; Rini Rini (STIKes Ibnu Sina Ajibarang, 2025)
Price fluctuations in agricultural commodities, including cocoa, are a common phenomenon that can be influenced by a variety of factors such as global market demand, seasonality, production volume, weather conditions, and product quality. These dynamic changes in prices can create uncertainty and directly impact the economic stability of farming households, especially in rural areas where agriculture is the primary source of income. This study aims to analyze the effect of cocoa price fluctuations on the welfare level of farmer households in Kaleok Village, Binuang Sub-district, Polewali Mandar Regency. The research adopts a descriptive quantitative approach with a field survey method to capture the lived experiences of cocoa farmers facing price instability. Primary data were gathered using a structured questionnaire based on a Likert scale from 74 respondents, selected through the Slovin formula to ensure representativeness. The data were analyzed using simple linear regression to determine the relationship between price volatility and welfare indicators such as income stability, access to education, healthcare, housing conditions, and overall quality of life. The findings reveal that cocoa price fluctuations significantly affect the welfare of farmer households. Higher fluctuations tend to reduce income certainty, limit household spending, and hinder long-term economic planning. These results emphasize the need for policy interventions such as price support mechanisms, farmer cooperatives, access to market information, and financial literacy programs. Ensuring price stability and strengthening institutional support could play a vital role in improving the economic resilience and living standards of cocoa farmers. This study contributes to the broader discourse on rural development, agricultural economics, and poverty reduction in Indonesia.